2005
DOI: 10.1292/jvms.67.801
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma hyopneumoniae in Lung and Nasal Swab Samples from Pigs by Nested PCR and Culture Methods

Abstract: ABSTRACT. We examined nasal swab and lung homogenate samples collected from pigs experimentally and naturally infected with Mycoplasma hyopneumoniae for the detection of M. hyopneumoniae by the nested PCR (nPCR) and culture methods. In the 23 experimentally infected pigs, M. hyopneumoniae was commonly detected in nasal swabs by the nPCR and culture methods at 4 weeks after inoculation, and there was a significant correlation (P<0.01) between the titers of viable organisms in nasal swabs and in lung homogenates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…To avoid false positive results due to contamination in the nPCR, appropriate positive and negative controls were used during DNA extraction and amplification. The results should be interpreted at the herd level, not at the individual level (Otagiri et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To avoid false positive results due to contamination in the nPCR, appropriate positive and negative controls were used during DNA extraction and amplification. The results should be interpreted at the herd level, not at the individual level (Otagiri et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…This diagnostic tool is suitable for detection of M. hyopneumoniae under field conditions in suckling pigs and nursery pigs (Otagiri et al, 2005;Sibila et al, 2007), and can detect 5.1 × 10 6 ng M. hyopneumoniae DNA or as few as four organisms/μl reaction mixture (Gebruers et al, 2008). To avoid false positive results due to contamination in the nPCR, appropriate positive and negative controls were used during DNA extraction and amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Verdin et al (2000) demonstrated that M. hyopneumoniae was probably confined to the lower respiratory tract in six-month-old pigs. Otagiri et al (2005) also found that lung sample detections were higher than in nasal swabs from the same animals.…”
Section: Methodsmentioning
confidence: 86%
“…However, this method is less practical because it requires special Friis medium and because the agent grows slowly. (Thacker 2004, Otagiri et al 2005. Additionally, other microorganisms that coexist in the sample might outgrow M. hyopneumoniae (Thacker 2004).…”
Section: Introductionmentioning
confidence: 99%
“…All these factors make isolation of the organism from ϐield samples even more difϐicult. Currently, the most frequently used techniques for M. hyopneumoniae diagnosis are the histological analysis of affected tissues, immunohistochemistry (IHC) and, more recently, polymerase chain reaction (PCR) (Mattson et al 1995, Calsamiglia et al 1999, Ribeiro et al 2004, Thacker 2004, Otagiri et al 2005. Samples used for histological techniques are routinely kept in a 10% formalin solution and the subsequently embedded in parafϐin (formalin-ϐixed, parafϐin-embedded -FFPE) (Srinivasan et al 2002, Coura et al 2005, Delfour et al 2006, Ferrer et al 2007, and pathology laboratories keep large collections of FFPE samples, allowing important retrospective studies using histological analysis (Ferrer et al 2007).…”
Section: Introductionmentioning
confidence: 99%